1999
DOI: 10.1177/106286069901400302
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Health-Related Quality of Life Following Elective Total Hip Replacement

Abstract: This study examined the patient perspective of surgical success through the measurement of health-related quality of life (HRQOL), in order to identify the patient characteristics and process issues associated with postoperative changes in health status. Patients completed the RAND 36-item Health Survey 1.0 (SF-36) prior to surgery and at 6 months following surgery. Baseline patient demographic and clinical information were collected from the medical record and were used to develop models of change in HRQOL fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
6
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
4
6
1
Order By: Relevance
“…Even when allowance is made for possible confounding effects, the long‐term improvement in the physical functioning of the cases is striking when set against the decline that occurred in controls. This observation is consistent with findings from other studies (2–13) and suggests that the benefits of THA are often substantial and sustained. In contrast, mental health improved less over followup, and no more in cases than in controls.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Even when allowance is made for possible confounding effects, the long‐term improvement in the physical functioning of the cases is striking when set against the decline that occurred in controls. This observation is consistent with findings from other studies (2–13) and suggests that the benefits of THA are often substantial and sustained. In contrast, mental health improved less over followup, and no more in cases than in controls.…”
Section: Discussionsupporting
confidence: 92%
“…At this time point, patients were found to have significantly worse physical functioning when compared with controls; older age at surgery and preoperative pain appeared to predict a worse physical outcome. This study is in accord with others in suggesting that the greatest benefit of surgery on quality of life relates to pain and physical functioning, but that improvements may also be found in social functioning and mental health (2–13). The treatment appears to be effective at all ages (2, 5, 13–15), with greater benefits in patients with poorer preoperative health‐related quality of life (2, 4, 16).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Many predictors of SF-36 scores have been investigated [5,9,10], the most common being preoperative SF-36 scores, which are positively correlated with improvement in SF-36 scores after surgery [11,12]. Some studies have suggested medical care characteristics (medication, type of prosthesis), physician-related characteristics (sex, experience) [13] and effective patient-physician communication [14] as potential predictors of improvement in SF-36 score. Indeed, if health problems and personal factors are major HRQoL determinants, environmental factors, as defined by The International Classification of Functioning, Disability and Health, are also major determinants.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, HRQOL is used as an outcome variable following specific interventions or events. For example, HRQOL has been used as an outcome measure following joint replacements (Benroth & Gawande, 1999; Fortin et al, 1999; Hopman, Mantle, Towheed, & MacKenzie, 1999; Jones, Voak‐lander, Johnston, & Suarez‐Almazor, 2000; Knutsson & Bergbom, 1999; Lieberman et al, 1997; O'Boyle, McGee, Hickey, O'Malley, & Joyce, 1992; Randell et al, 2000), hip fractures (Borgquist, Nilsson, Lindelow, Wiklund, & Thorngren, 1992; Randell et al, 2000), or other surgical procedures, such as prostatectomy or vascular surgery (Cleary, Greenfield, & McNeil, 1991; Hayward et al, 1999; Holtzman, Caldwell, Walvatne, & Kane, 1999; Mangione et al, 1997). HRQOL also has been used to assess the impact over time of specific diseases or problems, such as rheumatoid arthritis (Kosinski, Zhao, Dedhiya, Osterhaus, & Ware, 2000) or fear of falling (Cummings, Salkeld, Thomas, & Szonyi, 2000).…”
mentioning
confidence: 99%